Assessment of Micro Financial Institution Funding on the Performance of Small and Medium Enterprises in Murang’a County-Kenya - Mwangi, Njoki; Shisia, Adam; Mwai, Lilian; Okibo, Walter Bichanga (European Journal of Business and Management, 2014)
The fundamental purpose of this study was to assess the impact of Micro finance Institutions (MFIs) funding on the performance of Small and Medium Enterprises (SMEs) in rural Murang’a. Simple random sampling technique was employed in selecting the 50 SMEs that constituted the sample size of the research. Structured questionnaire was designed to facilitate the acquisition of relevant data which involves simple percentage graphical charts. Illustrations were tactically applied in data presentations and analysis. The findings of the study reveal that elements i.e. technology, management, training and financing were very crucial much as MFIs funding benefitted the SMEs even though only few of them were capable enough to secure the loan amount needed. Interestingly, majority of the SMEs acknowledged positive contributions of MFI funding towards promoting their market excellence and it is recommended that further research be carried out in other industries and countries in order to show whether there’s any link between MFI funding and performance on SMEs.
Keywords: Microfinance; Micro Finance Institutions; Small and Medium Enterprises